Physiological Essence of Magnesium in Plants and Its Widespread Deficiency in the Farming System of China - Ishfaq, Muhammad; Wang, Yongqi; Yan, Minwen; Wang, Zheng; Wu, Liangquan; Li, Chunjian; Li, Xuexian (Frontiers in Plant Science, 2022)
Magnesium (Mg) is an essential nutrient for a wide array of fundamental physiological and biochemical processes in plants. It largely involves in chlorophyll synthesis, production, transportation and utilization of photoassimilates, enzyme activation, and protein synthesis. As a multifaceted result of introduction of high-yielding fertilizer-responsive cultivars, intensive cropping without replenishment of Mg, soil acidification and exchangeable Mg (Ex-Mg) leaching, Mg has become a limiting nutrient for optimum crop production. However, little literature is available to better understand distinct responses of plants to Mg deficiency, the geographical distribution of soil Ex-Mg, and the degree of Mg deficiency. Here, we summarize the current state of knowledge of key plant responses to Mg availability and, as far as possible, highlight spatial Mg distribution and the magnitude of Mg deficiency in different cultivated regions of the world with a special focus on China. In particular, ~55% of arable lands in China are revealed Mg-deficient (<120 mg kg-1 soil Ex-Mg), and Mg deficiency literally becomes increasingly severe from northern (227-488 mg kg-1) to southern (32-89 mg kg-1) China. Mg deficiency primarily traced back to higher depletion of soil Ex-Mg by fruits, vegetables, sugarcane, tubers, tea, and tobacco cultivated in tropical and subtropical climate zones. Further, each unit decline in soil pH from neutral reduced ~2-fold soil Ex-Mg. This article underscores the physiological importance of Mg, potential risks associated with Mg deficiency, and accordingly, to optimize fertilization strategies for higher crop productivity and better quality.